2016
DOI: 10.1002/rcm.7503
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation and identification of amino acid containing membrane lipids using liquid chromatography/high‐resolution mass spectrometry

Abstract: Rationale Intact polar lipids (IPLs) are the building blocks of cell membranes, and amino acid containing IPLs have been observed to be involved in response to changing environmental conditions in various species of bacteria. High‐performance liquid chromatography/mass spectrometry (HPLC/MS) has become the primary method for analysis of IPLs. Many glycerol‐free amino acid containing membrane lipids (AA‐IPLs), which are structurally different than abundant aminophospholipids, have not been characterized using H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
(121 reference statements)
0
22
0
Order By: Relevance
“…The acylated amino acids GL and flavolipin have previously been identified in the membranes of several different members of the phylum Bacteroidetes (8,21,32). In this study, we have identified the genes required for the production of these acylated amino acids.…”
Section: Discussionmentioning
confidence: 92%
“…The acylated amino acids GL and flavolipin have previously been identified in the membranes of several different members of the phylum Bacteroidetes (8,21,32). In this study, we have identified the genes required for the production of these acylated amino acids.…”
Section: Discussionmentioning
confidence: 92%
“…The acylated amino acids, GL and flavolipin, have previously been identified in the membranes of several different members of the Phylum Bacteroidetes (8, 17, 32). In this study we have identified, for the first time, the genes required for the production of these acylated amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The dried extract residue was dissolved in hexane/2-propanol/H 2 O (718:271:10, v/v/v) injection solvent, filtered through a 0.45 µm, 4 mm diameter True TM Regenerated Cellulose syringe filter (Grace Davison) prior to injection and analysis. Extracted IPLs from the enrichment slurries were analyzed by high-performance liquid chromatography-electrospray ionization-ion trap mass spectrometry (HPLC-ESI/IT/MS) according to [34], with some modifications [35]. IPL abundance was assessed by integrating the HPLC-ESI/IT/MS mass chromatogram for each individual identified IPL, and areas were summed per IPL head group and reported per gram of slurry, dry weight.…”
Section: Intact Polar Lipid (Ipl) Extraction and Hplc-esi/it/ms Analysismentioning
confidence: 99%